The influence of isometric preload on power expressed during bench press in strength-trained men - Bartolomei, S.; Fukuda, D. H.; Hoffman, J. R.; Stout, J. R.; Merni, F. (European Journal of Sport Science, 2017)
The purpose of this study was to compare the power expressed during the bench press exercise in resistance-trained men following different pre-activation conditions. Twenty-two trained men (age 24.1 ± 1.7 years, height 178.6 ± 6.1 cm, body mass 81.1 ± 0.6 kg) completed a maximal effort bench press (1-RM) test (100.0 kg ± 8.1 kg). In a subsequent assessment, each participant performed concentric bench press movements with loads of 20%, 30%, 40% and 50% of their 1-RM preceded by either a concentric contraction (CC), a low isometric preload (LIP; 70% 1-RM) or a high isometric preload (HIP; 100% 1-RM) conditions. All movements were performed in a Smith machine with a settable quick-release device. Participants performed all three conditions in randomized fashion. Results indicated that power outputs during the bench press exercise following HIP were significantly (p < 0.05) greater than CC at 20% 1-RM (+9%), 30% 1-RM (+16%) and 40% 1-RM (+14%), and LIP at 20% 1-RM (+4%), 30% 1-RM (+20%) and 40% 1-RM (+15%). No differences were found between conditions at 50% 1-RM. Area under the force-power curve with HIP was greater (p < 0.05) than with CC and LIP. In conclusion, results of this study indicate that the use of a HIP (100% 1-RM) in trained participants results in significantly greater power output during the concentric phase of a multi-joint exercise when compared to standard concentric movement.